Konstruksi Identitas STEM (Science, Technology, Engineering, Mathematics) Siswa SMA: Studi Kasus di Pembelajaran Fisika - Putri, Febi Dwi; Purwaningsih, Endang; Munfaridah, Nuril (Universitas Nahdlatul Ulama Blitar, 2024)
STEM plays a very important role in the progress of a country. The choice of interest in work in the STEM field is influenced by STEM identity. The importance of STEM identity needs to be known for educational institutions to increase student interest in the STEM field. This research aims to describe the STEM identity construction of a high school student studying physics with independent curriculum guidelines. The type of research used is qualitative research with a case study method in the form of a single case study. Data collection was carried out through semi-structured interviews with one participant based on purposive sampling techniques. The data obtained was then confirmed through field notes during six physics learning meetings as a form of data triangulation. This research uses the STEM identity construct which includes three indicators. The main participant is a female student in class X high school who has a strong STEM identity among other students. The results of this study show that indicators of interest, recognition, and performance-competence influence the STEM identity construction formed by high school students. Increasing STEM identity can be done by optimizing the STEM approach in the independent curriculum.